Properties of sago starch-nanoclay biocomposites film - Abdul Razak, Nur Humairah; Ahmad, Zuraida (Trans Tech Publications, Switzerland, 2012)
This paper reported on properties of sago starch that was compounded with montmorillonite (MMT) nanoclay to form biodegradable composites film. The film was fabricated via film casting method with glycerol as a plasticizer. The investigated biocomposites film was prepared at starch-glycerol/MMT weight fraction of 90/10, 85/15, 80/20 and 75/25. The physical properties of the film, namely thickness and density were studied and results show that incorporation of nanoclay as filler affects the biocomposites physical properties. Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used to analyze the film’s morphological properties and chemical characteristics, respectively. SEM shows that less clay content in the film produces homogenous phase and well dispersed of clay platelets within the starch matrix. FTIR summarizes that MMT nanoclay is able to form hydrogen bonding with starch.